Evolução do grau de fadiga em pacientes com câncer de mama em tratamento radioterápico - Souto, Natasha Firmino (2014)
Radiotherapy is one of the most commonly used treatments in the fight against breast cancer. However, despite treating the disease, it also causes systemic side effects, of which malaise and fatigue are among the most presented. Therefore, we aimed to evaluate the evolution of the degree of fatigue in women with breast cancer undergoing radiotherapy. This is a longitudinal, prospective, descriptive study conducted in a cancer treatment center in Fortaleza-CE, Brazil, from November 2013 to January 2014, with a sample of 56 women undergoing adjuvant radiotherapy. Fatigue was present at the beginning, middle, and end of RT treatment, in 67.5%, 73.2%, and 91.1% of patients, respectively. The mild degree was the one that affected most patients in the three stages evaluated, with 51.7% in the beginning, 57.1% in the middle, and 71.4% at the end of treatment. Through the paired t-test, there was significant evolution of the degree of fatigue between the beginning and the end (p˂0.00) and between middle and end (p<0.00) of radiotherapy, both presented p<0.05. The most commonly reported symptoms among women who had fatigue were body ache in 9 (13.6%), and skin color changes after radiation in 8 (12.1%). The main causes they related to the onset of fatigue were commuting from home to the radiotherapy center reported by 17 patients (25.4%) and housework/daily activities by 12 (17.9%). The factors identified as those that most relieve fatigue were lie down/sleep for 26 (32.1) and bathe for 16 (19.1%). From the data analysis based on health care practice and literature, we concluded that the main factor that triggered or even enhanced this fatigue was not only the radiotherapy added to the disease itself, rather the socioeconomic factors. Among these are the lower family income and labor or domestic activity associated with the mode of transport to perform the treatment and the waiting time to accomplish it.